Consolidated financial statements in light of the Hungarian regulations and the IFRS standards - Alexandra Szekeres; Angelika Dienes (Competitio)
Companies today have diverse relationship systems. In a legal sense, individual companies exercising influence on each other engage in significant transactions with each other during their operations. Market participants require knowledge of the financial, monetary, and income status of these corporate groups. Therefore, in addition to individual annual reports, it is also important to prepare consolidated financial statements that present the group as a single entity, following either national or international accounting standards.